ENVIRONMENTAL ECONOMIC VALUATION AND THE SYSTEM OF NATIONAL ACCOUNTS FOR GREEN GROSS DOMESTIC PRODUCT CALCULATION: A BIBLIOMETRIC ANALYSIS BETWEEN 1945 AND 2022 - Saraiva Nazareno dos Anjos, Sérgio; Barreto Gois, Alexsandro; de Souza Freire, Fátima; Madeira Nogueira, Jorge (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract This article is a theoretical essay that presents the state-of-the-art relationship between Environmental Economic Valuation and the System of National Accounts (SNA), unifying accounting, and economic elements to develop future indicators for Green Gross Domestic Product (Green GDP) calculation. Several studies have emerged to define, classify, and measure ecosystem services in recent decades. Nevertheless, there are still gaps in the quantification and disclosure of natural capital. The quantification of natural capital is essential in the System of Environmental-Economic Accounting (SEEA). By including environmental information in the traditional SNA, the SEEA makes it possible to estimate macroeconomic aggregates more rigorously for the Green GDP. Methods and procedures are needed to make these estimates viable that allow monetary assessment of ecosystem goods and services that do not have a market price and the depletion or depreciation of the stock of resources that make up the national ecological heritage. This paper is exploratory and quantitative research based on a bibliometric analysis of scientific publications on GDP, Green GDP, and economic valuation from 1945 to 2022, prospected on the Web of Science database. There are publications on the proposed theme on all continents, emphasizing Europe, Asia, North America, and Africa, and the low representation of South America. There are a predominance of universities and Research and Development (R&D) organizations among the institutions. Some retrieved documents are papers published by institutions that do not develop R&D activities like the financial system, showing interest in the subject aiming for competitiveness in its market. There is a need for further research to develop and validate indicators to obtain Green GDP, including the natural capital. The ratification of several international agreements and protocols related to the environment also can stimulate the application of economic valuation methods to guarantee the adequate inclusion of environmental assets in the calculation of national wealth.